Упростите выражение 2(X/2+y/4)^2+(2x-y)^2

0 голосов
53 просмотров

Упростите выражение 2(X/2+y/4)^2+(2x-y)^2


Алгебра (34 баллов) | 53 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

2(\frac{x}{2}+\frac{y}{4})^{2}+(2x-y)^{2}=

2(\frac{x^{2}}{4}+2*\frac{x}{2}*\frac{y}{4}+\frac{y^{2}}{16})+4x^{2}-4xy+y^{2}=

\frac{x^{2}}{2}+\frac{xy}{2}+\frac{y^{2}}{8}+4x^{2}-4xy+y^{2}=

\frac{9x^{2}}{2}+\frac{9y^{2}}{8}-\frac{7xy}{2}=4,5x^{2}+1,125y^{2}-3,5xy

(32.6k баллов)
0 голосов

2(x/2+y/4)^2+(2x-y)^2=2*(x^2/4+0.25xy+y^2/16)+(2x-y)^2=0.5x^2+0.5xy+0.125y^2+(2x-y)^2=0.5x^2+0.5xy+0.125y^2+4x^2-4xy+y^2=4.5x^2+0.5xy+0.125y^2-4xy+y^2=4.5x^2-3.5xy+0.125y^2+y^2=4.5x^2+1.125y^2-3.5xy

(13.7k баллов)